2012
DOI: 10.1111/j.1600-0609.2012.01819.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal aspects of thalassaemia a changing paradigm

Abstract: Beta-thalassaemia is characterised by progressive anaemia necessitating regular blood transfusions to sustain life. With the advent of effective chelating agents that can reduce the iron burden and extend patients' survival, renal disease, as in other ageing populations, has become more prevalent. In recent years, chronic kidney disease (CKD) has become overwhelming; indeed, approximately 8% or 6 million people of the UK population has evidence of CKD. Several factors, which occur in patients with thalassaemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
12

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 84 publications
(130 reference statements)
3
35
0
12
Order By: Relevance
“…The long-term survival of children with thalassemia has improved dramatically with respect to both life expectancy and quality of life. 9 This is partly attributable to improved treatment regimens, including regular blood transfusions and iron chelation therapy. However, though the quality of life in patients with b-TM has improved significantly, this success has permitted the emergence of previously unrecognized complications and morbidities of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The long-term survival of children with thalassemia has improved dramatically with respect to both life expectancy and quality of life. 9 This is partly attributable to improved treatment regimens, including regular blood transfusions and iron chelation therapy. However, though the quality of life in patients with b-TM has improved significantly, this success has permitted the emergence of previously unrecognized complications and morbidities of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that chelation therapy can potentially lead to nephrotoxicity via an unknown mechanism. 9 Therefore, monitoring of renal functions in transfusiondependent thalassemic patients receiving chelation therapy has been recommended. 1 The detection of renal damage has been made by traditional biomarkers such as serum creatinine and blood urea nitrogen (BUN), and this has remained unaltered for a few decades.…”
Section: Introductionmentioning
confidence: 99%
“…315 Mechanisms of kidney dysfunction are numerous and only partially clarified, but chronic anemia, hypoxia, iron, and iron chelators are potentially toxic to renal parenchyme. 316 Acute kidney injury has also been reported, and the probable mechanism in many cases is prerenal from sepsis or complications of HF (cardiorenal syndrome) and liver failure that affects renal perfusion. Labile iron may also lead to acute kidney injury.…”
Section: Renal Diseasementioning
confidence: 99%
“…1,2 Pada thalassemia dijumpai kelainan yang bersifat herediter akibat mutasi gen globin yang menyebabkan berkurangnya atau tidak terdapat sintesis satu atau lebih rantai globin. 1,3 Dalam praktek klimis dikenal dua tipe thalassemia, yaitu thalassemia α dan thalassemia β. Thalassemia α diakibatkan oleh berkurang atau tidak terdapat sintesis α -globin, sedangkan thalassemia β diakibatkan berkurang atau tidak terdapat sintesis β -globin. 3 Terapi dengan transfusi darah disertai pemakaian kelasi besi baik tunggal maupun kombinasi mengakibatkan peningkatan angka harapan hidup penderita thalassemia.…”
Section: Pendahuluanunclassified
“…Penderita thalassemia dapat mengalami gangguan pada ginjal sebagai akibat anemia kronik, kelebihan besi sebagai efek samping transfusi jangka panjang dan sebagai efek samping pemakaian kelasi besi. 1,3,4 Anemia kronik dapat menyebabkan peningkatan stres oksidatif dan lipid peroksidase yang dapat menyebabkan kerusakan pada sel tubulus ginjal. Anemia kronik juga menyebabkan berkurangnya resistensi vaskular sehingga terjadi peningkatan aliran darah pada ginjal dan meningkatkan laju filtrasi golerulus yang dikenal sebagai hiperfiltrasi.…”
Section: Pendahuluanunclassified